The Development of the Regional Oak Tree-Ring Chronology from the Roman Sites in Celje - Durman, Aleksandar (2007)
Notable among the numerous analyses carried out by the Laboratory of Dendrochronology at Cornell are those of the wooden posts in the Kupa riverbed in the environs of today's Sisak in Croatia. The remains of a Late Roman wooden bridge as well as a short section of via publica Celeia-Poetovio material from Sisak was significantly crossdated with material from Slovenia. This gives us an enormous potential to crossdate oak material from different parts of the Balkan peninsula and also encourages further research in this region.